2023
DOI: 10.3390/ani13060976
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Colostrum Supplementation Modulates the Intestinal Microbial Community in Rabbits

Abstract: BC is a nutraceutical that can modulate intestinal microbiota. This study investigates the effects of BC diet supplementation on luminal and mucosa-associated microbiota in the jejunum, caecum, and colon of rabbits. Twenty-one New Zealand White female rabbits were divided into three experimental groups (n = 7) receiving a commercial feed (CTRL group) and the same diet supplemented with 2.5% and 5% BC (2.5% BC and 5% BC groups, respectively), from 35 (weaning) to 90 days of age (slaughtering). At slaughter, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Gut bacterial communities are able to influence the absorption of both essential and non-essential elements and, vice versa, the elements are able to modulate the microbiota [ 68 ]. It is widely known for several species, such as rabbits [ 69 ], chickens [ 70 ], cows [ 71 ], that the gut microbiota is largely influenced by the feeding regimen. For example, studies have demonstrated that bacteria such as Lactobacillus johnsonii and Lactobacillus reuteri have the ability to modulate Fe homeostasis [ 72 ]; meanwhile, the effects of Fe supplementation are still little known; in general, Fe is not considered a limiting element in today’s animal production, and some research has found that Fe supplementation increases the presence of beneficial microbiota [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gut bacterial communities are able to influence the absorption of both essential and non-essential elements and, vice versa, the elements are able to modulate the microbiota [ 68 ]. It is widely known for several species, such as rabbits [ 69 ], chickens [ 70 ], cows [ 71 ], that the gut microbiota is largely influenced by the feeding regimen. For example, studies have demonstrated that bacteria such as Lactobacillus johnsonii and Lactobacillus reuteri have the ability to modulate Fe homeostasis [ 72 ]; meanwhile, the effects of Fe supplementation are still little known; in general, Fe is not considered a limiting element in today’s animal production, and some research has found that Fe supplementation increases the presence of beneficial microbiota [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…At slaughter, the digestive tract was removed from each animal; tissue samples of each section (jejunum, caecum, and colon) and a mesenteric lymph node were collected with the use of a sterile scalpel and stored in 2 mL sterile tubes in RNAlater ® (Sigma-Aldrich, St. Louis, MO, USA). Samples were stored at −80 °C until processing, as previously described [ 35 ]. The content of each intestinal tract was collected in a 2 mL sterile tube and immediately frozen at −20 °C until use.…”
Section: Methodsmentioning
confidence: 99%
“…Microbial profiles based on 16S rRNA amplicon-based sequencing for all the animals, intestinal tracts, and diets have already been presented elsewhere (Agradi et al, 2023 [ 35 ]). Briefly, the bacterial DNA was extracted using a QIAamp PowerFecal Pro DNA Kit (Qiagen, Hilden, Germany), amplified following the 16S Metagenomic Sequencing Library Preparation Protocol (Illumina, San Diego, CA, USA), and sequenced on a MiSeq (Illumina) instrument with 2 × 250-base paired-end reads run.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the large intestine shows the highest richness and diversity in bacterial species, while the small gut has the highest variability in the gastrointestinal tract of rabbits [13]. Several studies have been performed to evaluate the effects of the quality and levels of the diet [16,17], dietary supplementation with nutraceuticals [18][19][20], the temperature of the drinking water [21], age [22], and weaning period [23]. The fecal microbiota and its functional capacity associated with weaning weight in meat rabbits [24], hygiene of the environment [25], season [15], and drug treatments [26,27] have been investigated.…”
Section: Introductionmentioning
confidence: 99%